Job-to-Job Flows and Earnings Growth - Hahn, Joyce K.; Hyatt, Henry R.; Janicki, Hubert P.; Tibbets, Stephen R. (American Economic Review, 2017)
The US workforce has had little change in real wages, income, or earnings since the year 2000. However, even when there is little change in the average rate at which workers are compensated, individual workers experienced a distribution of wage and earnings changes. In this paper, we demonstrate how earnings evolve in the US economy in the years 2001-2014 on a forthcoming dataset on earnings for stayers and transitioners from the U.S. Census Bureau's Job-to-Job Flows data product. We account for the roles of on-the-job earnings growth, job-to-job flows, and nonemployment in the growth of U.S. earnings.